Theoretical Computer Science - Preparata, F.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
R.E. Miller: Parallel program schemata.- D.E. Muller: Theory of automata.- R. Karp: Computational complexity of combinatorial and graph-theoretic problems.
Keywords: Mathematics; Information theory; Mathematics; Operations Research, Management Science; Theory of Computation